Non-Muslim Consumers’ Online Purchase Intention towards Halal Food in Manila - Cruz, Racquel Untalan; Billanes, Rico A. (Indonesian Journal of Halal Research, 2021)
Aside from Muslims, who expends halal products due to devout obligations, it is understood that non-Muslims have also started eating halal food. The fact could be explained by the increased number of consumers ready to purchase halal products. This paper aims to determine and investigate the online purchase intention among Filipino non-Muslim consumers toward halal food. Four models were tested using multiple regression analysis, and the quantitative research method was used to investigate perceived risk, trust and confidence, website design quality, and online shopping enjoyment. Perceived risk has been identified to be the most significant in predicting factors in an online purchase intention of halal food. Furthermore, the study found that trust, confidence, and perceived risk strongly influence online purchase intentions. Therefore, future studies should also include variables such as consumer habits and knowledge of halal food.